Undergraduate Research and Economic Development: A Systems Approach in Wisconsin. Issue 169 (March 2015) - Van Galen, Dean; Schneider‐Rebozo, Lissa; Havholm, Karen; Andrews, Kris
Abstract : This chapter presents the state of Wisconsin and the University of Wisconsin System as an ongoing case study for best practices in systematic, intentional, statewide programming and initiatives connecting undergraduate research and economic development.